2012
DOI: 10.1177/0145721711432456
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs for Social Support and Effects on Diabetes Self-care Activities in Korean Americans With Type 2 Diabetes

Abstract: Objective-The purpose of this study was (1) to characterize the primary sources of social support and the extent of unmet needs for support (defined as the gap between social support needs and the receipt of social support) in a sample of Korean Americans (KAs) with type 2 diabetes and (2) to examine the effect of unmet needs for support on their self-care activities.Methods-Baseline data obtained from a community-based intervention trial were used for this study of 83 middle-aged KAs with type 2 diabetes. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 39 publications
5
94
0
2
Order By: Relevance
“…Gender roles disparity may offer one possible explanation of low adherence in Korean Chinese. Married Korean Chinese women emphasized the role of as the primary nurturer and adopted a self-sacrificing mentality more than those in other Asian countries (Song et al, 2012). As compared to Chinese women, their Korean counterpart was given a role that might burden them more in caring for the family, which involved multiple responsibilities pushing them to prioritize supporting the family than their own health (Ahn et al, 1998;Song et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender roles disparity may offer one possible explanation of low adherence in Korean Chinese. Married Korean Chinese women emphasized the role of as the primary nurturer and adopted a self-sacrificing mentality more than those in other Asian countries (Song et al, 2012). As compared to Chinese women, their Korean counterpart was given a role that might burden them more in caring for the family, which involved multiple responsibilities pushing them to prioritize supporting the family than their own health (Ahn et al, 1998;Song et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Married Korean Chinese women emphasized the role of as the primary nurturer and adopted a self-sacrificing mentality more than those in other Asian countries (Song et al, 2012). As compared to Chinese women, their Korean counterpart was given a role that might burden them more in caring for the family, which involved multiple responsibilities pushing them to prioritize supporting the family than their own health (Ahn et al, 1998;Song et al, 2012). Studies regarding gender role strain of Korean women can be observed not only in preventive health behaviors but also in chronic disease managements (Ahn et al, 1998;Yoo and Kim, 2010;Park and Kim, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a barrier might be overcome by changing to insulin pens and better healthcare provider communication [25]. [26]. In a previous study, women tended to have more negative perceptions of insulin therapy than did men [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de la demanda de información, los pacientes requerían que esa información se proporcionara de manera respetuosa y progresiva, evitando los mensajes alarmistas 23 . Asimismo, Song y col 31 , en su estudio, obtuvieron diferencias entre sexos en re-An. Sist.…”
Section: Qué Tipo De Información Y Recursos Demandan Los Pacientes Counclassified